Jews, Liberalism, Antisemitism: A Global History - Green, Abigail; Levis Sullam, Simon (Palgrave Critical Studies of Antisemitism and Racism, 2020)
1. Introduction: Jews, Liberalism, Antisemitism: Towards a 21st Century History- Abigail Green and Simon Levis Sullam -- Part 1: The Limits of Liberalism -- 2. Liberalism and Antisemitism: A Reassessment from the Peripheries- Lisa M. Leff -- 3. Osman Bey’s The Conquest of the World by Jews (1873): a Liberal Antisemitism? - Simon Levis Sullam -- 4. Jews and Other Others- Ari Joskowicz -- Part 2: Living Liberalism -- 5. The Material of Race: Caribbean Jews, Clothing, and Manhood in the Age of Emancipation and Liberal Revolution- Laura Leibman -- 6. Liberalism, Antisemitism and Everyday Life in Vienna: The Tragic Case of Heinrich Jaques (1831-1894)- Jonathan Kwan -- 7. Giving and Dying in Liberal Italy: Jewish Men and Women in Italian Culture Wars -Luisa Levi D’Ancona -- Part 3: Rethinking East-West -- 8. Unsettling the “Jewish Question” from the Margins of Europe: Spanish Liberalism and Sepharad- Michal Rose Friedman -- 9. A Model Millet? Ottoman Jewish Citizenship at the End of Empire -Julia Phillips Cohen -- 10. From East to West: America as the Liberal Melting Pot of Jewish Politics- Matt Silver -- Part 4: Liberalism, Empire, Zionism -- 11. Who Introduced Liberalism into the Damascus Affair (1840)? Center, Periphery, and Networks in the Jewish Response to the Blood Libel- Yaron Tsur -- 12. A Jewish “Liberal” in Istanbul: Vladimir Jabotinsky, the Young Turks, and the Zionist Press Network, 1908-1911- Ozan Ozavci -- 13. Jews, Imperial Liberalism, and the Predicament of “Small Nations”: Lewis B. Namier’s Gentry Nationalism- Arie M. Dubnov -- Part 5: Making, Unmaking, and Remaking Liberalism -- 14. 1848 and Beyond: Jews in the National and International Politics of Secularism and Revolution- Abigail Green -- 15. “A Certain Kind of Liberalism”: Jewish Minority Rights in Eastern Europe and Beyond- James Loeffler -- 16. The Jewishness of Cold War Liberalism- Malachi Haim Hacohen. -17. Afterword.